Model Collaborative Governance dalam Pengawasan Orang Asing di Kota Baubau - Asman Safitra; La Ode Syaiful Islamy; Rahmawati Rahmawati; Rininta Andriani (Program Studi Ilmu Pemerintahan, 2026)
This study aims to analyze cross-sectoral collaboration in the supervision of foreign nationals at the Class II Non-TPI Immigration Office in Baubau, using the collaborative governance approach. Employing a descriptive qualitative method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that foreign nationals supervision in Baubau has undergone significant transformation through the establishment of the Foreigners Supervision Team (TIM PORA), serving as a coordination forum among various institutions such as Immigration, Police, Military, and Kesbangpol. The study identifies the four pillars of collaborative governance: initial conditions that were previously sectoral and unstructured; institutional design through TIM PORA, though lacking a comprehensive inter-agency MoU; collaborative processes characterized by open communication and flexible coordination; and facilitative leadership conducted inclusively by the Immigration Office. This collaboration has enhanced inter-agency synergy and supervision effectiveness, evidenced by jointly resolved immigration violation cases. Nevertheless, challenges persist, including overlapping authorities, limited operational regulations, and resource constraints. The study confirms the relevance of collaborative governance as an effective, responsive, and adaptive model for managing foreign nationals supervision amidst the complexities of globalization and transnational mobility.